How to interpret and manage abnormal liver blood test results in older people. (2nd August 2021) - Subhani, Mohsan; Sheth, Abhishek; Ahmad, Bilal; Ryder, Stephen
Abstract : Ageing impairs liver function and reduces the liver's regenerative capacity. With the predicted increase in the older population, the burden of liver disease will proportionally rise in this age group. Elevated levels of liver enzymes in an otherwise asymptomatic older individual (≥65 years) are a common observation and positively associated with the metabolic syndrome, whereas a decline in albumin levels is linked with a rise in all-cause and liver-specific mortality. Deranged liver function tests do not always indicate liver disease, nor do normal liver function tests exclude liver disease. Therefore, clinicians need to consider individual patient risk factors during the assessment of abnormal liver function tests. This article discusses various liver function tests, their pathophysiology, and the approach to interpret and manage common abnormalities in liver function test results and liver disease in the older population.